2009
DOI: 10.2298/ciceq0901037m
|View full text |Cite
|
Sign up to set email alerts
|

The application of microwaves in essential oil hydrodistillation processes

Abstract: The influence of microwaves pre-treatment of raw plant materials (wooded greenery and fruits of conifers-fir, spruce, pine, juniper and Douglas fir) on the kinetics of the essential oil hydrodistillation using the Unger-type apparatus was studied. These plant materials are important feedstocks in the Republic of Srpska, as they could be used for the industrial production of essential oils for pharmaceutical, cosmetic and food industries. The main goal was to find out how the microwave pre-treatment of the raw … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Militias et al have done comparative studies on the chemical composition of EOs from plant extracts of conifers and was revealed with major modification. MAE has given 50% better yield of EOs and rate of flow with less time of extraction as compared to HD . Similarly, by using sonication waves in UAE, the kinetics was described in different ways.…”
Section: Comparative Overviewmentioning
confidence: 99%
“…Militias et al have done comparative studies on the chemical composition of EOs from plant extracts of conifers and was revealed with major modification. MAE has given 50% better yield of EOs and rate of flow with less time of extraction as compared to HD . Similarly, by using sonication waves in UAE, the kinetics was described in different ways.…”
Section: Comparative Overviewmentioning
confidence: 99%
“…Although less well described in the literature, an alternative approach for utilizing microwave heating of plant based materials has been to treat the materials with microwave energy prior to conventional extraction processes (Miletic, et al 2009). Microwave preconditioning of sugar cane prior to juice diffusion studies led to significant decreases in colour and significant increases in juice yield, Brix %, purity and Pol % (Brodie, et al 2011).…”
Section: Microwave Assisted Extractionmentioning
confidence: 99%
“…Although less well described in the literature, an alternative approach for utilizing microwave heating of plant based materials has been to treat the materials with microwave energy prior to conventional extraction processes [110]. Microwave preconditioning of sugar cane prior to juice diffusion studies led to significant decreases in colour and significant increases in juice yield, Brix %, purity and Pol % [111].…”
Section: Microwave Assisted Extractionmentioning
confidence: 99%